2000
DOI: 10.1029/1999gl010968
|View full text |Cite
|
Sign up to set email alerts
|

A physically‐based treatment of elemental carbon optics: Implications for global direct forcing of aerosols

Abstract: To date, global models of direct radiative forcing have treated elemental carbon (EC) as completely externally mixed or well‐mixed internally. No global study has treated EC as a core in an internal mixture. It is hypothesized that the well‐mixed treatment is unphysical and reality lies between the externally‐mixed and core treatments. It is also suggested, but not proven, that most EC particles are coated to some degree; hence, the core treatment may be more representative than the external‐mixture treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
389
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(412 citation statements)
references
References 39 publications
21
389
1
1
Order By: Relevance
“…Second, hygroscopic growth factors are smaller for SDE particles than for the common JFJ aerosol (Weingartner et al, 2001). Third, it has been shown that the wavelength dependence of the absorption coefficient is very similar in the 0.45-1.0 µm region for externally mixed, internally mixed and shell-core configurations of black carbon (Jacobson, 2000). Since the aerosol reaching the JFJ is aged and therefore internally mixed, α ap will probably exhibit only a slight variation with humidity.…”
Section: Resultsmentioning
confidence: 99%
“…Second, hygroscopic growth factors are smaller for SDE particles than for the common JFJ aerosol (Weingartner et al, 2001). Third, it has been shown that the wavelength dependence of the absorption coefficient is very similar in the 0.45-1.0 µm region for externally mixed, internally mixed and shell-core configurations of black carbon (Jacobson, 2000). Since the aerosol reaching the JFJ is aged and therefore internally mixed, α ap will probably exhibit only a slight variation with humidity.…”
Section: Resultsmentioning
confidence: 99%
“…It is now well established that neglecting morphological properties by employing over-simplified shape models, such as the homogeneous sphere approximation, can significantly impair estimates of the direct climate, forcing impact of aerosols (Jacobson 2000;Kahnert et al 2007). However, increasing the complexity of model particles is no guarantee for yielding better estimates of the optical properties (Veihelmann et al 2006).…”
Section: Properties Of Externally Mixed Lacmentioning
confidence: 99%
“…The past three decades have seen increasing interest in black carbon (BC) and elemental carbon (EC), both of which originate from the incomplete combustion of carbonaceous combustibles, due to their strong light-absorbing properties and their possible health effects (Johnson and Huntzicker 1979;Wolff 1981;Turco et al 1983;Molnar et al 1999;Jacobson 2000Jacobson , 2001Ramanathan and Carmichael 2008;Allen et al 2012). EC represents thermally refractory carbon with a graphitic structure, whereas BC is commonly used to define the extent to which an aerosol sample exhibits light-absorbing properties (Salako et al 2012;Gray and Cass 1998;Huntzicker et al 1982;Watson et al 2005).…”
Section: Introductionmentioning
confidence: 99%